Microarchitecture of the subcommissural organ of goat* - KUMAR, PAWAN; KUMAR, SURAJ; SINGH, YASHWANT (The Indian Journal of Animal Sciences, 2013)
The histomorphology of sub commissural organ was studied in male goats (6-9 months age ). A pseudostratified columnar ciliated ependyma lining the organ showed 6-10 rows of type -I and II ceJls. The subependymal glial zone contained basal cytoplasmic processes of ependymal cells, blood capillaries and few glial cells. The hypendyma had type -I and II hypendymal cells. Reissner's fibre was located on free ependymal surface. The present study shall establish the basis to explore histoenzymological. ultra -structural and neuro endocrinological importance of the organ.